Generalized Hypergraph Matching via Iterated Packing and Local Ratio - Parekh, Ojas; Pritchard, David (Approximation and Online Algorithms, 2015)
In k $$k$$ -hypergraph matching, we are given a collection of sets of size at most k $$k$$ , each with an associated weight, and we seek a maximum-weight subcollection whose sets are pairwise disjoint. More generally, in k $$k$$ -hypergraph b $$b$$ -matching, instead of disjointness we require that every element appears in at most b $$b$$ sets of the subcollection. Our main result is a linear-programming based (k-1+1k) $$(k-1+\tfrac{1}{k})$$ -approximation algorithm for k $$k$$ -hypergraph b $$b$$ -matching. This settles the integrality gap when k $$k$$ is one more than a prime power, since it matches a previously-known lower bound. When the hypergraph is bipartite, we are able to improve the approximation ratio to k-1 $$k-1$$ , which is also best possible relative to the natural LP. These results are obtained using a more careful application of the iterated packing method. Using the bipartite algorithmic integrality gap upper bound, we show that for the family of combinatorial auctions in which anyone can win at most t $$t$$ items, there is a truthful-in-expectation polynomial-time auction that t $$t$$ -approximately maximizes social welfare. We also show that our results directly imply new approximations for a generalization of the recently introduced bounded-color matching problem.We also consider the generalization of b $$b$$ -matching to demand matching, where edges have nonuniform demand values. The best known approximation algorithm for this problem has ratio 2k $$2k$$ on k $$k$$ -hypergraphs. We give a new algorithm, based on local ratio, that obtains the same approximation ratio in a much simpler way.